Report on professional attachment - Civil Aviation Authority of Singapore, Singapore Aviation Academy. - Kang, Mui Koon. (2009)
The purpose of this report is to provide a summary on the Professional Attachment with the Singapore Aviation Academy, a division of Civil Aviation Authority of Singapore. The first chapter of the report will look into the general background on the Civil Aviation Authority of Singapore, Singapore Aviation Academy and International Relations Unit. The second chapter will cover the different projects undertaken and the experiences gained during the attachment. The last chapter will present an overview of the Singapore Aviation Academy, a conclusion on the attachment and recommendations.